Impact of Creative Thinking on the Effectiveness of Administrative Decision-Making Process: A Field Study from Top and Middle Management Perspective at Insurance Companies Operating in Jordan - Sweidat, Ahmed; Alshaikh, Fuad (Jordan Journal of Business Administration, 2017)
This study aimed to measure the impact of creative thinking with the five dimensions (fluency, flexibility, originality, elaboration and sensitivity to the problems) on the effectiveness of administrative decision-making process in insurance companies operating in Jordan. The researcher contacted 24 insurance companies out of 28 companies operating in Jordan. Two hundred and seventy (270) questionnaires were distributed to top - and middle - level management employees working at these companies. After different follow ups with the respondents, the researcher was able to return 218 usable questionnaires. To achieve the objectives of the study, the researcher designed a questionnaire, consisting of three parts, where the first part included questions about the company and demographic characteristics, while the second part contained 25 paragraphs measuring the availability of the five dimensions of creative thinking. The third part included (11) paragraphs measuring the level of effectiveness of administrative decision-making process. The study reached the following findings: There was a high level of statistical significance at the significance level (α ≤ 0.05) for the availability of creative thinking with its five dimensions at insurance companies operating in Jordan and there was a high level of statistical significance at the level of significance (α ≤ 0.05) for the effectiveness of administrative decision-making process at insurance companies operating in Jordan. In light of these findings, the following recommendations are made: Providing continuous training in the development of creative thinking skills for managers in order to update their knowledge and skills about the latest developments in this field, keeping all managerial levels involved in the decision-making process and providing chances for them to be updated in the latest developments of decision-making processes and techniques. Doing so is more likely to reduce resistance, increase the degree of acceptance and facilitate the implementation of the decision - making process without future barriers.